Sequence Analysis and Expression of the Phosphoprotein (P) Gene of a less Virulent Newcastle Disease Virus (D58) Isolated from an Unvaccinated Village Chicken - Raj, Vivitha; Kirubaharan, John. J.; Chandramohan, Andrew (International Journal of Poultry Science, 2009)
The P gene of a less virulent Newcastle disease virus isolated from unvaccinated village chicken was studied in detail. This D58 isolate had a coding sequence of 1188 nucleotides coding for 395 amino acids. The site for RNA editing for the evolution of the V and W proteins was found to be at positions 402 at the nucleotide and 134 at amino acid levels. The P gene has two N-Glycosylation sites at positions 126 and 288; one glycosaminoglycan attachment site at position 307, six protein kinase C phosphorylation sites at positions 72, 125, 203, 235, 345 and 369 and ten casein kinase II phosphorylation sites at positions 3, 18, 83, 91, 138, 229, 239, 291, 374 and 381. The D58 isolate was grouped with the other lentogenic strain B1 in the phylogentic analysis. On comparison with 23 other NDV strains/isolates, the P gene sequences of NDV was observed to be evolved with same pattern of substitutions and there is not much evolutionary divergence. The mean evolutionary diversity for entire population of NDV strains/isolates was estimated to be only 0.147. The phosphoprotein gene was expressed in a prokaryotic vector and strong antibody response against recombinant phosphoprotein was reported in the serum of vaccinated birds in ELISA.